Targeting ErbB-2 nuclear function induces the interferon signalling pathway in breast cancer - Cordo Russo, Rosalia Ines (2021)
ErbB2, a member of ErbB family of receptor tyrosine kinases, is an oncogenic driver in breast can-cer (BC). Despite clinical efficiency of ErbB2-targeted therapies (trastuzumab, TZ), resistance to drugs is a major issue. ErbB2 is a membrane-bound receptor, but also migrates to the nucleus (NErbB2) to act as a transcription factor/coactivator.